Backward Design: An Approach to the Professional Development of School Leaders - Shiat Lu, Wong (Innovare Journal of Education, 2023)
Influential leaders are one of the essential elements to achieving the goals of school transformation. Optimizing the ability of school leaders requires opportunities to practice what they have learned from the training module of the School Transformation Program 2025 (TS25). Since the results of the school’s achievements can convince the community to support and cooperate with the school, the researcher adopted an approach known as the backward design as a model for the professional development of school leaders. First, however, the researcher needs to examine the feasibility and appropriateness of this approach. Therefore, the researcher conducted a School Leaders Perception Study (SLPS) through a questionnaire to survey 225 leaders’ perceptions of 82 Kota Kinabalu district schools about implementing the TS25 program in Malaysia. This survey was administered through a google form to gauge school leaders’ acceptance level of TS25 program implementation. It also aims to identify the need for self-development among school leaders, which they usually implement through best practice sharing. In addition, the researcher also studied the willingness of school leaders to implement TS25 partnerships targeted at the community through the questionnaire. After determining the reliability of the SLPS questionnaire, the results of descriptive analysis showed that Kota Kinabalu district school leaders strongly agreed with school transformation implemented according to the school context. Most of them also agree that partnership implementation is a valuable learning opportunity in professional development. The findings also indicate that targeted TS25 partnerships with the community should begin from the results of existing school achievements. Therefore, the researcher suggests a backward design approach as an innovative approach for school leaders’ professional development.